Validation of food frequency questionnaire for food intake of adults in Gida, West, Ethiopia - Fikadu, Worku; Mulugeta, Segni; Dejene, Yeshimebet (Frontiers in Public Health, 2024)
BackgroundDiet is characterized by complex exposure to strongly intercorrelated components. Early efforts to understand diet-disease associations focused on the role of specific nutrients, but later, it became evident that dietary exposures may act synergistically in several instances. For research into how nutrition affects health and disease, scientifically sound descriptions of dietary intake at the population level are essential. Although food frequency questionnaires are important nutritional assessment methods, they should be validated and checked for reliability according to the eating habits of the specific population. Context-specific tools are needed to estimate food intake accurately, but a single study in Ethiopia has not established reliability. Hence, this study aimed to establish a valid and feasible dietary assessment method for 24-h dietary recall.ObjectiveTo adapt and validate FFQs for use as dietary assessment tools in epidemiological studies among adults in Gida woreda, West Ethiopia.MethodA community-based cross-sectional study was conducted from February 15–30, 2023, among 150 participants. Data were collected through an interviewer-administered questionnaire, a focus group discussion, and a key informant interview. We compared the mean of three interactive 24-h dietary recalls to the FFQ to assess its relative validity. By comparing food category levels, mean differences, medians, and cross-classifications from the FFQ and a 24-h dietary recall, validity was assessed.ResultsThe response rate of this study was 100% for both the FFQ and 24-item dietary recall. The mean (±SD) age of the participants was 37.6 9.7 years. Of the total participants, 40 (29%) were between 31 and 35 years old. Sixty-four (42%) of the study participants were protestant religious followers. The median ranges from zero for meat and poultry to 1,930 for cereal, as estimated by the 24-h dietary recall method. The median ranges from 14 mg/day for meat and poultry to 724 mg/day for cereal, as estimated by the FFQ.ConclusionThis study revealed that this food frequency questionnaire had good validity for capturing the intake of food groups which indicated by their value: vegetables (0.8), legumes (0.9), roots/tubers (0.8), cereal (0.5), dairy products (0.75), and meat/poultry (0.64) at both the individual and group levels. Hence, it is recommended for health care providers to use FFQ as a tool for studying and managing dietary-related diseases.